Microbiological Assessment of Street Foods: Detection of Staphylococcus aureus and Salmonella spp Using Selective Culture Methods - Liss Dyah Dewi Arini; M. Ekahidayatullah; Annisa Rahmawati; Anggraini Sih Prabandari; Mahjanah Husein (Biosel Biology Science and Education, 2026)
Food safety remains a major public health concern due to the risk of contamination by pathogenic microorganisms. Street food, which is widely consumed, has a high potential for microbiological contamination due to inadequate hygiene and sanitation practices. This study aimed to detect and estimate the presence of presumptive Staphylococcus aureus and presumptive Salmonella spp. in street food samples. A quantitative descriptive laboratory approach was employed using the spread plate method on selective media, namely Mannitol Salt Agar (MSA) and Sorbitol MacConkey Agar (SMAC). Ten types of street food samples were analyzed using serial dilutions (10⁻¹, 10⁻², and 10⁻³) with duplicate treatments. The results showed that most samples exhibited high levels of microbial contamination, with Total Plate Count (TPC) values ranging from 0 to 2.16 × 10⁶ CFU/g. Several samples exceeded the maximum microbial contamination limit of 10⁴ CFU/g established by the Food and Drug Supervisory Agency (BPOM). The presence of colonies morphologically identified as presumptive Staphylococcus aureus and presumptive Salmonella spp. indicates potential contamination by pathogenic bacteria. These findings suggest that street food may pose a risk to public health if hygiene and sanitation practices are not properly maintained. Therefore, improved food handling practices and monitoring are necessary to ensure food safety. Keywords: Food Safety, Street Food, Staphylococcus aureus, Salmonella spp., Total Plate Count, Microbial Contamination